Familia Pontellidae (Crustacea: Copepoda) en la Bahía La Ventosa, Oaxaca, México: Sistemática y ecología - Álvarez Silva, Carlos (2003)
A study on ecological records of planktonic copepods from The Ventosa Bay, Oaxaca, Mexico is presented. Five species were identified: Labidocera acuta, L. lubbockii, Pontella agassizi, P. tenuiremis and Pontellina plumata. The most abundant species was L. acuta and their copepodite stages conforming the 95.7% of Pontellids, followed by L. lubbockii 4.09%; other species were less than one percent. The reproductive success of L. acuta is probably favored by its resistance to the changes in temperature and salinity, because of it is an eurytherme and euryhaline organism. Total density of this family was between 18 and 472 copepods/100 m3 in 1987 and 1988. Nevertheless in 1992 and 1993 the density was between 490 to 123 030 copepods/100 m3. This copepod density increment could be related local phenomenon (upwelling) at the beginning and end of the year.